Statistical prediction of parametric roll using FORM. (1st November 2017) - Jensen, Jørgen Juncher; Choi, Ju-hyuck; Nielsen, Ulrik Dam
Abstract: Previous research has shown that the First Order Reliability Method (FORM) can be an efficient method for estimation of outcrossing rates and extreme value statistics for stationary stochastic processes. This is so also for bifurcation type of processes like parametric roll of ships. The present paper discusses this solution procedure with a focus on the computational efficiency of FORM as compared with Monte Carlo Simulation (MCS). Highlights: Two effective optimization procedures are presented. Fast and accurate predictions of parametric roll are validated by extensive Monte Carlo simulations. The appearance of several critical wave episodes for the same roll threshold angle is compared with Monte Carlo simulations.